2016
DOI: 10.1017/s0030605316000624
|View full text |Cite
|
Sign up to set email alerts
|

How rare is rare? Quantifying and assessing the rarity of the bush dog Speothos venaticus across the Amazon and other biomes

Abstract: The bush dog Speothos venaticus is a mediumsized Neotropical canid. It is considered to be rare and its biology and population parameters are still poorly understood. The Amazon is one of the main strongholds of this species and is important for maintaining viable populations, as the region still holds extensive tracts of pristine habitat. We gathered field data from camera-trap studies throughout the Brazilian Amazon to estimate the relative abundance of the species and gain an understanding of its rarity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Abundance in the specific caatinga scrub habitat was even lower, at 0.081 records/100 trap-days. Thus, it is possible to conclude that, given the relatively low relative abundance, this felid is rare in both the biome and specific habitat of the Brazilian Caatinga (see Oliveira et al, 2018). In the tropical deciduous forest of southern Puebla, Mexico, margay abundance was found to be 0.112 records/100 trap-days (Farías et al, 2015), similar to that found in this study.…”
supporting
confidence: 79%
“…Abundance in the specific caatinga scrub habitat was even lower, at 0.081 records/100 trap-days. Thus, it is possible to conclude that, given the relatively low relative abundance, this felid is rare in both the biome and specific habitat of the Brazilian Caatinga (see Oliveira et al, 2018). In the tropical deciduous forest of southern Puebla, Mexico, margay abundance was found to be 0.112 records/100 trap-days (Farías et al, 2015), similar to that found in this study.…”
supporting
confidence: 79%
“…We used the R language with environment for statistical computing (R Development Core Team, 2018) to generate figures and analysis presented in this study. We also used the package Igraph (Csardi & Nepusz, 2006) in R (R Development Core Team, 2018) to graphically display the interactions among single or mixed, edible or inedible substances and families of mammals that were attracted by substances.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of monitoring and evaluating the distribution and abundance of mammals in ecosystems, there remains a lack of consistency and standardization in the methods used in studies in tropical regions (Ahumada, Hurtado, & Lizcano, 2013; Munari, Keller, & Venticinque, 2011). This is particularly the case of mammal species that may have low densities, large home ranges, are discrete and elusive, coupled with the logistical difficulties encountered in most tropical regions, often limiting the approach of studies that can be used (de Oliveira et al., 2018; du Preez, Loveridge, & Macdonald, 2014; Laurance, 1992; Michalski, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This minimum 30-min interval reduces the temporal dependence between camera trap detections [45] and has been widely used in studies with camera traps [4749]. Vertebrates were identified using field guides of mammals and birds [50–52].…”
Section: Methodsmentioning
confidence: 99%
“…In order to estimate the relative abundance of vertebrates, we considered as independent, videos with over a 30 min interval, when the same species was recorded during the same day on the same camera [ 7 , 45 , 46 ]. This minimum 30-min interval reduces the temporal dependence between camera trap detections [ 45 ] and has been widely used in studies with camera traps [ 47 49 ]. Vertebrates were identified using field guides of mammals and birds [ 50 – 52 ].…”
Section: Methodsmentioning
confidence: 99%